Proclus on the Forms as Paradigms in "Plato’s Parmenides: The Neoplatonic Response to Aristotle and Alexander of Aphrodisias’ Criticisms" - Melina Mouzala (Revista de Filosofia Antiga, 2022)
This paper sets out to analyze Proclus’ exegesis of Socrates’ suggestion in Parmenides 132d1-3 that Forms stand fixed as patterns (παραδείγματα), as it were, in the nature, with the other things being images and likenesses of them. Proclus’ analysis of the notion of being pattern reveals the impact of the Aristotelian conception of the form as paradigm on his views, as we can infer from Alexander of Aphrodisias’ and Simplicius’ explanation of the paradigmatic character of the Aristotelian form. Whereas Aristotle and Alexander of Aphrodisias refute the efficient causality of the Platonic Forms and support that μέθεξις is just a metaphor, Syrianus, Proclus and Asclepius defend the Platonic theory, and specifically Proclus, who brings to the fore the multilateral role of the Forms as patterns with regard to the secondary things of this realm.[1]